Growth performance, nutrient digestibility and carcass characteristics of grower rabbits fed graded levels of Bamboo (Bambusa vulgaris) leaf meal (International Journal of Agricultural Research, Innovation and Technology, 2023)
This study aimed to determine the growth performance, nutrient digestibility and carcass characteristics of grower rabbits fed diets containing graded Bambusa vulgaris leaf meal (BVLM) levels. Thirty rabbits weighing an average of 999 g were allocated in a Completely Randomized Design (CRD) to five treatments (BVLM 0%, which was the control diet, BVLM 5%, BVLM 10%, BVLM 15% and BVLM 20%) with six replicates. The rabbits were adapted to the assigned diets for one week and fed for ten weeks.  Feed intake, live weight changes and feed conversion ratio were the performance parameters measured.  Existing market prices for feed items were used to appraise the diets economically. A digestibility study was undertaken during the 10th week. No mortality was recorded during the study. Before termination of the feeding trial, 15 rabbits (3 from each treatment) were selected randomly, taken off feed for 24 hours and humanely slaughtered. Carcass parameters and weights of internal organs were measured and recorded. Results revealed that live weight changes, feed intake and feed conversion ratio were similar for all treatments. However, the cost of feed/kg and feed/kg gain decreased linearly with an increase in the inclusion level of BVLM. The results also showed that BVLM could be utilized in up to 15% of grower rabbit diets without lowering nutrient digestibility and dressing percentage. It was concluded that BVLM could be used up to 20% of the diet of grower rabbits to reduce the cost of feed/kg and cost of feed/kg gain without any adverse effects on live weight changes and weights of internal organs.Int. J. Agril. Res. Innov. Tech. 13(1): 6-14, June 2023